2013
DOI: 10.1080/13803395.2013.847906
|View full text |Cite
|
Sign up to set email alerts
|

The role of cognitive reserve in cognitive aging: Results from the neurocognitive study on aging

Abstract: The study tested the cognitive reserve hypothesis by quantifying cognitive reserve (CR) and subsequently determining its role in executive function and verbal episodic memory performance. A neuropsychological battery was administered to 383 Greek-Cypriot older adults. A multiple indicators multiple causes (MIMIC) latent construct was utilized to define CR incorporating three indicators: years of education, vocabulary, and reading performance. Findings from two structural equation models supported the moderatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 56 publications
7
46
0
2
Order By: Relevance
“…As previously reported, participants in the Neurocognitive Study on Aging who have 10 years of education or more, besides reporting higher levels of QoL, also demonstrated significantly enhanced cognitive performance [12,13]. Similarly, in other large cohort studies, such as the Mac Arthur Studies on Cognitive Aging, higher education levels typically led to cognitively challenging professional careers which in turn may support privileged lifestyles [8] with good resources for improved physical and psychological health, better environmental support and promote subjective sense of well-being.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…As previously reported, participants in the Neurocognitive Study on Aging who have 10 years of education or more, besides reporting higher levels of QoL, also demonstrated significantly enhanced cognitive performance [12,13]. Similarly, in other large cohort studies, such as the Mac Arthur Studies on Cognitive Aging, higher education levels typically led to cognitively challenging professional careers which in turn may support privileged lifestyles [8] with good resources for improved physical and psychological health, better environmental support and promote subjective sense of well-being.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, the same review of studies recognizes that women experience a decline in fluid intelligence at a younger age than men, thus, potentially increasing cognitive disability for a population which tends to outlive its male counterparts. Variables such as years of formal education and quality of cognitive engagement can moderate the effects of aging via the creation of cognitive reserve, the mind's ability to implement strategies and counteract the presence of pathology [13]. Additionally, higher educational levels typically lead to cognitively challenging professional careers, which, in turn, may support privileged lifestyles and promote a subjective sense of well-being [8].…”
Section: Introductionmentioning
confidence: 99%
“…This and other studies also support the role that neurocognitive activity and stimuli play in preventing or abating the development of such neurocognitive deficits in lieu of such neuropathological burden (Vance, Roberson et al, 2010). Giogkaraki and colleagues (2013) found that with age, the greater amount of neurocognitive reserve was predictive of greater preservation of episodic memory and executive function. In their study, a combination of measures of reading ability, vocabulary, and years of education served as the proxy measure for neurocognitive ability.…”
Section: Neurocognitive Reservementioning
confidence: 95%
“…This study shows that stimuli and environmental challenges may cause neurobiological changes which influence neurocognitive reserve. Other studies in humans also suggest that neurocognitive stimuli may increase neurocognitive reserve and protect one from developing neurocognitive impairments (Giogkaraki et al, 2013; Wilson et al, 2013). …”
Section: Neurocognitive Reservementioning
confidence: 97%
“…Giogkaraki et al [11] tested the CR hypothesis by quantifying CR. A neuropsychological battery was administered to 383 Greek-Cypriot older adults.…”
Section: Measurement Of Crmentioning
confidence: 99%